2011
DOI: 10.1176/ps.62.7.pss6207_0753
|View full text |Cite
|
Sign up to set email alerts
|

A Learning Collaborative of CMHCs and CHCs to Support Integration of Behavioral Health and General Medical Care

Abstract: Even though numerous systemic barriers were encountered, the findings support existing literature indicating that the learning collaborative is a viable quality improvement approach for enhancing integration of general medical and mental health services between CHCs and CMHCs. Real-world implementation of evidence-based guidelines presents challenges often absent in research. Technical resources and support, a stable workforce with adequate training, and adequate opportunities for collaborator communications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Very few details were provided on the techniques that were taught. In some studies, the LC purveyors had already identified potential areas for improvements that sites should consider for their QI projects (e.g., domains in the chronic care model, system improvements, known implementation barriers) (7, 18, 31, 33). In addition to didactic training related to practices and QI methods, four of the studies reported that individual sites presented information to other participating QI teams during the in-person sessions (7, 15, 27, 37).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Very few details were provided on the techniques that were taught. In some studies, the LC purveyors had already identified potential areas for improvements that sites should consider for their QI projects (e.g., domains in the chronic care model, system improvements, known implementation barriers) (7, 18, 31, 33). In addition to didactic training related to practices and QI methods, four of the studies reported that individual sites presented information to other participating QI teams during the in-person sessions (7, 15, 27, 37).…”
Section: Resultsmentioning
confidence: 99%
“…However, there were a few studies that did provide some detail about the use of QI methods. In those LCs, the faculty set forth possible improvement areas from which site could develop their PDSAs or provided hands on coaching and support (7, 17, 18, 2931, 34, 37, 38). One study, did not include PDSAs, but rather provided teams with a template to develop “work plans” to facilitate the integration of mental health and primary care in school based health centers (39).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations